Shanghai Cooperation Organization and the New World Order - Habova, Antonina (Research Papers, 2018)
The study aims at analyzing the major characteristics of the Shanghai Cooperation Organization as a different type of international organization that provides an unprecedented platform for dialogue and communication between states of different religious and cultural tradition, social systems, and ideologies. The conclusion is that - against the backdrop of China’s rise as a global power and increasing tensions in the international system – the model of SCO functioning as a platform for interaction, for sharing and converging positions could be a successful formula for establishing an alternative regional order with the ambition to extend its scope to a global level. Methodologically, the study builds on an interdisciplinary approach that allows assessing the problem in historical, legal, economic, and diplomatic aspect.